Etyczne postawy przedsiębiorców regionu tarnobrzeskiego. Studium z socjologii moralności - Rogowski, Robert (Annales. Etyka w Życiu Gospodarczym, 2011)
The article presents results of empirical research made amongst entrepreneurs of the Tarnobrzeg region concerning moral dimension of their activities. A few hundred persons were examined (mainly owners of small companies). They were asked about their businesses in moral aspect. Entrepreneurs work hard, have respect to other people and try to be honest. Most important values for them are family, health and love. The work is also very important for entrepreneurs, but they complain about lack of free time.